How have digital resources been utilised in times of COVID-19? Opinions of medical students based in the United Kingdom. - Lau, Edward Jun Shing; Aslam, Aiman; Arshad, Zaki (Canadian Medical Education Journal, 2020)
The COVID-19 outbreak halted medical education in its tracks, with medical students across all years finding their upcoming placements and in-person teaching cancelled in a bid to abide to social distancing regulations, for the safety of staff, students and patients alike. As United Kingdom (UK)-based medical students, we have witnessed our medical school’s attempts to preserve our education by turning to digital technology, allowing for remote teaching over the four months. This article describes some of the steps taken across the UK to uphold education during such uncertain times and provides an insight into UK medical students’ perspectives on the prolonged and increased reliance on learning via digital technology, highlighting perceived benefits and areas for improvement. In doing so, we hope to contribute to the discussion of how digital technology may best be used in medical education in the future.